Development of a novel leg-wheel module with fast transformation and leaping capability. (September 2021) - Chen, Hsuan-Yu; Wang, Ting-Hao; Ho, Kuang-Chan; Ko, Chuan-Yu; Lin, Pai-Chen; Lin, Pei-Chun
Highlights: A novel module capable of fast transforming its shape between a wheel and a leg. The maximum leg length approximately 3.4 times the wheel radius. Can perform wheel-to-leap behavior. Leaping height up to 4.6 times the wheel radius. Abstract: We report on the development of a novel two-degrees-of-freedom module capable of transforming its shape between a wheel and a leg, with the length of the latter approximately 3.4 times the wheel radius. The leg-wheel module was empirically built and experimentally evaluated. It utilizes a linkage mechanism and can perform a smooth yet rapid leg-wheel transition within 0.25 s. The design concept, selection of the linkage parameters, and kinematics are described in this paper. The rapid transition from a wheel to a leg endows the robot with wheel-to-leap behavior. The general motion planning strategy of the leg-wheel, as well as the wheel-to-leap behavior, are explained in the demonstration example. The results confirm that the module can perform wheel-to-leap behavior with a height of up to 4.6 times the wheel radius.